Pengembangan Multimedia Interaktif dengan Aplikasi Prezi Berbasis Lingkungan untuk Meningkatkan Hasil Belajar Kognitif Materi Siklus Air di Kelas V Sekolah Dasar - Puspita Sari, Yeni (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to determine feasibilitymaterial, language, media, and student responses, as well as product effectiveness resulting from the development of interactive multimedia with environment-based prezi applications to improve cognitive learning outcomes in elementary school science learning. This research is a Research and Development (R&D) study. The model used in development is the ADDIE model.The subjects in the study were studentsSDN 78 Bengkulu Selatan, which amounted to 20 students of class V as the control class, and 20 students of class V SDN 73 Bengkulu Selatan as the experimental class. The instruments used in this study were interview guides, questionnaires, and tests of understanding this concept in the form of multiple choice questions through pretest and posttest. The data analysis technique in this study was validation analysis using Aiken's V andreliabilityInterrater Reliability, teacher and student responses, as well as quantitative analysis using N-gain. From the research results it is known that the results of material, language, and media validation, as well as students' responses tointeractive multimedia with the prezi applicationvery feasible and well used in learning so that students are happy and interested in learning. effectiveness resultsinteractive multimedia with the prezi applicationeffectively influence students' understanding of science concepts. Based ongain-score test ofinteractive multimediagives the results of a moderate gain score of 62%. So that students understand the concept of science using interactive multimediawith the prezi appenvironment-based to improve cognitive learning outcomes is higher than students who only use textbooks from schools so that it is declared effective.